Cu isotopes in groundwater for hydrogeochemical mineral exploration: A case study using the world-class Mount Isa Cu–Pb–Zn deposit (Australia). (January 2023) - Mahan, B.; Mathur, R.; Sanislav, I.; Rea, P.; Dirks, P.
Abstract: Copper is the crux resource in the transition to renewable energy sources, with green technologies such as solar panels, wind turbines and batteries all relying on this critical metal for their componentry, and more importantly for connection to electrical grids. While demand intensifies, copper discovery rates continue to fall due to increased scarcity of deposits that are outcropping and/or detectable by conventional means. This has engendered novel methods of detecting Cu-bearing ore under cover, such as hydrogeochemical analyses to trace ore mineral interaction with natural waters. This notably includes the development of Cu isotope systematics in natural waters, wherein proximal to Cu-bearing ore bodies enrichment of water in the heavier Cu isotope occurs (e.g. from oxidative weathering), thus providing a fingerprint of water interaction with Cu-bearing sulfides. Here, Cu isotope compositions for eighteen groundwater samples overlying and distal to the world-class, sediment-hosted stratiform Mount Isa Cu–Zn–Pb deposit were analyzed to assess the utility of groundwater Cu isotope compositions as an exploration tool for Cu-bearing ore under cover. A further 12 chalcopyrite Cu isotope compositions were determined from two drill cores directly overlying the main Cu-bearing ore body, to establish a baseline Cu isotope composition for the Mt Isa deposit. Cu isotope data were synthesized together with field water parameters and placed within a geological context to construct a framework for interpretation. When accounting for industrially impacted sites and underlying geology, results show a clear trend towards heavy Cu isotope enrichment in groundwater proximal to known mineralization, with enrichments of ∼1 per mil (‰) or more relative to distal groundwater and primary deposit chalcopyrite. These results corroborate and expand upon similar work from surface and groundwater samples around porphyry, exotic and IOCG Cu-bearing deposits. Moreover, these results strongly indicate that groundwater Cu isotope systematics for exploration under cover has great potential as a vectoring tool, illustrating that thus far the technique is applicable across deposit types. Highlights: Groundwater/chalcopyrite δ 65 Cu values are reported for the Mt Isa Cu–Pb–Zn deposit. Proximal groundwater samples display positive δ 65 Cu excursions relative to distal. Water and bore parameters effectively discriminate industrially impacted waters. δ 65 Cu and basic water/bore details comprise an efficient/effective exploration tool. Future exploration should apply hydrogeochemical δ 65 Cu for vectoring under cover.